Digital touch for remote personal communication: An emergent sociotechnical imaginary. (January 2021) - Jewitt, Carey; Leder Mackley, Kerstin; Price, Sara
This article makes legible emergent social imaginaries of digital touch for remote communication in personal relationships, with attention to digital touch interfaces. It draws on data from rapid prototyping research workshops with apprentice professionals embedded within digital communication. Touch is discussed with respect to four analytical themes: materiality, body, emplacement and temporality. We illustrate how participants' past and present experiences and future visions of remote digital touch thread through these themes and weave together to form a hegemonic, emergent sociotechnical imaginary of digital touch. The article contributes to social debates within digital personal remote communication by foregrounding touch, the material and the sensorial. The article's novel interdisciplinary framework (combining design-based rapid prototyping with a multimodal and multi-sensorial analysis within the frame of the sociotechnical imaginary) also contributes to methodology around future-facing phenomena, prior to the process of their solidification into material, political formations.